2003
DOI: 10.1191/0960327103ht332oa
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of biochemical and histopathological effects of Mentha piperita L. and Mentha spicata L. on kidney tissue in rats

Abstract: Peppermint plants have been used as a herbal medicine for many conditions, including loss of appetite, common cold, bronchitis, sinusitis, fever, nausea, vomiting and indigestion. This study is aimed at investigating the biochemical and histological effects of Mentha piperita L., growing in the Yenisar Bademli town of Isparta City, and Mentha spicata L., growing on the Anamas high plateau of Isparta City, on rat kidney tissue. Forty-eight male Wistar albino rats weighing 200 / 250… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
1
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 27 publications
1
41
1
1
Order By: Relevance
“…However, for this, studies would be needed to ascertain the ideal doses that could be used without harming the organism. Some studies with this herb have shown no alterations in urea, creatinine, catalase, superoxide dismutase, glutathione peroxidase levels and no nephrotoxicity, but may be related with decreased iron absorption rats (Akdogan et al, 2003(Akdogan et al, , 2004.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, for this, studies would be needed to ascertain the ideal doses that could be used without harming the organism. Some studies with this herb have shown no alterations in urea, creatinine, catalase, superoxide dismutase, glutathione peroxidase levels and no nephrotoxicity, but may be related with decreased iron absorption rats (Akdogan et al, 2003(Akdogan et al, , 2004.…”
Section: Discussionmentioning
confidence: 95%
“…This indicates the pressing need for new studies to clarify the real effects of medicinal plants and to provide scientific evidence establishing their usefulness. Mentha piperita (Family Labiatae; genus Mentha) is one of the ten most widely used plants in Brazil (Cortez et al, 1999) and is commonly used in the treatment of loss of appetite, common cold, bronchitis, fever, nausea, vomiting (Akdogan et al, 2003), spasmodic responses (Lu et al, 2002), and antimicrobial and antioxidant activities (Romero-Jimenez et al, 2005;Mimica-Dukic et al, 2005). Due to the important role of high plasma lipids in the development of insulin resistance, atherogenesis and cardiovascular disease, and the widespread use of M. piperita as a complementary and alternative medicinal intervention, this study aimed to investigate the effects of tea and juice prepared with fresh peppermint leaves (which is how the population uses this plant) on Wistar rats plasma lipids.…”
Section: Introductionmentioning
confidence: 99%
“…The aqueous whole plant extract did not affect the haematograms of the rats in a manner that would suggest adverse effects on their bone marrow, which is a source of recticulocytes. Some herbal remedies equally have hepato and nephro toxic effects [10,3]. Damage to these organs often results in the elevation of clinical chemistry parameters such as serum enzymes and analytes; some serum enzymes include aspartate aminotransferase (AST) and alanine aminotransferase (ALT), and some analytes include total and conjugated bilirubin, urea, and creatinine [1,3,7,14].…”
Section: Discussionmentioning
confidence: 99%
“…Some herbal remedies equally have hepato and nephro toxic effects [10,3]. Damage to these organs often results in the elevation of clinical chemistry parameters such as serum enzymes and analytes; some serum enzymes include aspartate aminotransferase (AST) and alanine aminotransferase (ALT), and some analytes include total and conjugated bilirubin, urea, and creatinine [1,3,7,14]. The significant reduction in alkaline phosphatase levels by administration of the aqueous extract shows that no possible cholestasis occurred at the dose levels tested since a rise in plasma ALP level is usually a characteristic finding in cholestatic liver disease [4].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Mentha piperita is one of the ten most widely used plants in several countries [6] and is commonly used in the treatment of loss of appetite, common cold, bronchitis, fever, nausea, vomiting [2], spasmodic responses [15], and antimicrobial and antioxidant activities [16,18].…”
Section: Introductionmentioning
confidence: 99%